The Influence of Work Environment and Workload on Turnover Intention at WBeauty Aesthetic Center Medan - Lasman Eddy Bachtiar; Togu Harlen Lumban Raja; Nurdaini Saputri Samosir (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study examines the influence of the work environment and workload on employee turnover intention, a beauty clinic that has faced a 10% turnover rate over the past year. Such a condition indicates a notable challenge in retaining skilled and experienced staff in the beauty service sector. The research specifically aims to analyze how the quality of the work environment and the level of workload affect employees’ intentions to leave their jobs. Using a quantitative approach, data were collected through questionnaires and analyzed using multiple linear regression, along with validity and reliability tests to ensure data accuracy. The analysis results reveal that the work environment has a significant and negative effect on turnover intention, meaning that a better work environment reduces employees’ desire to resign. Meanwhile, the workload shows no significant effect, although a positive trend is observed, implying that heavier workloads may increase turnover intention slightly. The findings emphasize the importance of maintaining a supportive and comfortable work environment as a key strategy to enhance employee retention in the beauty services industry.